Agonist and antagonist effects of tobacco-related nitrosamines on human α4β2 nicotinic acetylcholine receptors - Brusco, Simone; Ambrosi, Paola; Meneghini, Simone; Becchetti, Andrea (Frontiers in Pharmacology, 2015)
Regulation of the ‘neuronal’ nicotinic acetylcholine receptors (nAChRs) is implicated in both tobacco addiction and smoking-dependent tumor promotion. Some of these effects are caused by the tobacco-derived N-nitrosamines, which are carcinogenic compounds that avidly bind to nAChRs. However, the functional effects of these drugs on specific nAChR subtypes are largely unknown. By using patch-clamp methods, we tested 4-(methylnitrosamine)-1-(3-pyridyl)-1-butanone (NNK) and N’-nitrosonornicotine (NNN) on human α4β2 nAChRs. These latter are widely distributed in the mammalian brain and are also frequently expressed outside the nervous system. NNK behaved as a partial agonist, with an apparent EC50 of 16.7 μM. At 100 μM, it activated 16 % of the maximal current activated by nicotine. When NNK was co-applied with nicotine, it potentiated the currents elicited by nicotine concentrations ≤ 100 nM. At higher concentrations of nicotine, NNK always inhibited the α4β2 nAChR. In contrast, NNN was a pure inhibitor of this nAChR subtype, with IC50 of approximately 1 nM in the presence of 10 μM nicotine. The effects of both NNK and NNN were mainly competitive and largely independent of Vm. The different actions of NNN and NNK must be taken into account when interpreting their biological effects in vitro and in vivo.